2011
DOI: 10.2174/187152711796235023
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers as Novel Systems for Delivery of Neuropharmaceuticals to the Brain

Abstract: Most of the newly developed drugs fails to achieve sufficient bioavailability in to brain due to low water solubility and low permeability. Drug delivery systems are one method for achieving entry of molecules to their desired site of action within the body. Dendrimers are the customizable nanopolymers with uniform and well-defined particle size and shape. Dendrimers are of eminent interest for biomedical applications because of their ability to cross cell membranes. This potential pharmaceutical delivery syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…Dendrimers are a new class of hyperbranched and nanoscale macromolecules that possess an array of distinctive features including a welldefined globular architecture, narrow polydispersity and tunable surface functionalities. A typical dendrimer consists of a core molecule, monomeric branches called dendrons and surface functional groups that are able to react with other compounds (7)(8)(9)(10). Poly(amidoamine) (PAMAM)…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers are a new class of hyperbranched and nanoscale macromolecules that possess an array of distinctive features including a welldefined globular architecture, narrow polydispersity and tunable surface functionalities. A typical dendrimer consists of a core molecule, monomeric branches called dendrons and surface functional groups that are able to react with other compounds (7)(8)(9)(10). Poly(amidoamine) (PAMAM)…”
Section: Introductionmentioning
confidence: 99%
“…In particular, biotin has been chosen as a targeting molecule for small molecule transport through the blood-brain barrier in central nervous system disorder diagnosis and therapy. 15,16 The targeting of cancer cells with biotin-dendrimer conjugates for cancer therapy and cancer diagnosis is a promising field of investigation because of the much higher cellular uptake of the cisplatin-loaded biotinylated PAMAM dendrimers and the bifunctional conjugate (dendrimer-biotinfluorescein isothiocyanate) into ovarian cancer cell lines 17,18 and HeLa cells than seen for the conjugate without biotin. 19 It has been reported that biotin uptake is provided by the sodium-dependent multivitamin transporter present in many cells, including human keratinocytes, blood mononuclear cells, and epithelial cells of intestine, liver, and kidney.…”
mentioning
confidence: 99%
“…Compared with linear polymeric analogues such as PEG and HPMA the highly branched and globular architecture of these dendritic macromolecules exhibit properties such as increased water solubility, very low intrinsic viscosity and nanosize as well as increased cellular uptake and longer blood circulation time leading to increased drug accumulation at the target site (tumour). Positively charged poly(amidoamine) (PAMAM), poly(ethyleneimine) (PEI) and poly(propyleneimine) (PPI) denrimers can complex with DNA as gene carrier while their potential use in the delivery of drug across biological membranes such as transdermal (189), intestinal epithelia cells (190), human placenta (191) and blood-brain barrier (192)(193)(194) are currently being investigated. They exhibit features such as modifiable surface groups, multifunctional moieties and monodispersed nanoscale size.…”
Section: Dendrimersmentioning
confidence: 99%